Feminisation of radical Islam - Bartoszewicz, Monika Gabriela (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Women are considered a modernising factor in Islam. For decades the active and vocal Muslim feminists represented a progressive and liberating force challenging the traditional understanding of women in Islam and spearheading the efforts aimed at widening the spaces where females could exercise their full potential. Radical Islam, to the contrary, was believed to be and thus portrayed, as inherently masculine and necessarily patriarchal enterprise, somewhat oppressive when it came to women or at least defending the traditional status quo with regards to gender relations and roles. This paper provides an analysis of an emerging trend whereby Muslim women are not only active in the modernising circles but, quite the opposite, become vocal proponents of radical political Islam. Hence, instead of being the much hoped for progressive force, they constitute an avant-garde of the opposite: radical agenda advocating and actively supporting the agenda of political Islam; also in the sphere of political violence. This paper examines how feminisation of radical Islam progressed over time and shows how what hitherto represented a solely masculine privilege and domain, now also belongs to women. Where at first women were not present, with time they became pliable instrument in political struggle, only to gain their own independent voice, agency and a power to act autonomously
Keywords: polityka; kobiety; islam; przemoc polityczna